Creation of a database on BIM technology, building design - Aizhan Makulbekova (Foundations and Trends in Research, 2024)
Currently, low-rise residential buildings (cottages, townhouses) have become widespread on the territory of the Republic of Kazakhstan in suburban areas, which are significantly remote from the central districts of cities and settlements. In most cases, heating and gas networks are not provided in such areas, the power of electric networks is insufficient, which forces the use of modern energy-saving technologies to provide buildings with heat. In areas with poorly developed infrastructure, a reliable modern thermal energy source when building housing is heat pumps (HP), which use heat from renewable natural sources.(soil mass, groundwater, water from reservoirs, outdoor air, etc.).